HOUSING AND HEALTH: AN EXPLORATION OF HOUSING NEED IN CHILDREN WITH MEDICAL COMPLEXITY. (18th May 2018) - Hounsell, Kara Grace; Orkin, Julia; Cohen, Eyal; Soscia, Joanna; Netten, Kathy; Zahavi, Arielle
Abstract: BACKGROUND: Children with medical complexity (CMC), are defined by at least one chronic condition, functional limitation requiring technology support, multiple subspecialist involvement, and high healthcare utilization. A potentially significant social determinant that has yet to be examined in this population is that of "housing need." According to the Canada Mortgage and Housing Corporation, "housing need" refers to housing that is crowded, unaffordable, or in need of major repairs. Given the known associations between housing and health, we hypothesize that housing need could be particularly relevant in CMC. Population-specific housing considerations may include in-home medical services, housing space, and disability accommodations. OBJECTIVES: 1) Determine the prevalence of housing need in families with CMC and 2) Explore the experience and meaning of housing need of caregivers of CMC. DESIGN/METHODS: We conducted a mixed methods study using questionnaires and semi-structured interviews. Recruitment occurred through a tertiary paediatric hospital. Research ethics board approval was obtained. All participants were English-speaking primary caregivers of CMC living in the same household. Questionnaires were completed in person, by phone, or online via REDCap, a secure data collection application. Questionnaires explored safety, affordability, and accommodations and were analyzed using descriptive statistics. Following the questionnaire, participants were invited to be interviewed in person or by phone. Interview questions were developed iteratively and were analyzed using grounded theory. RESULTS: Of the 354 eligible caregivers, 93 participated in the questionnaire. A total of 36 caregivers (40%) reported some difficulties paying for housing each month. In addition, 56 participants (62%) described unmet need for accommodations (i.e. a lift, toilet accommodations, etc.). A total of 65 participants (83%) reported that their child's condition(s) affected their preferred housing location, while 55 participants (70.5%) felt it affected their preferred housing type. Of the fifteen interviews completed, several themes emerged including limited housing options for families with CMC and financial, physical, and mental health consequences of housing challenges. In addition, caregivers felt counseling was lacking on 1) safe evacuation and 2) housing requirements, such as space and equipment, as children age. CONCLUSION: This is the first in-depth exploration of housing need amongst families of CMC. Challenges identified include affordability, disability accommodations, and restrictions on housing type and location due to children's illnesses. Clinicians can support families of CMC by offering counseling on evacuation planning and common housing requirements for CMC.